Housing, Health, and Happiness - Cattaneo, Matias D.; Galiani, Sebastian; Gertler, Paul J.; Martinez, Sebastian; Titiunik, Rocio (2012)
We investigate the impact of a large-scale Mexican program to replace dirt floors with cement floors on child health and adult happiness. We find that replacing dirt floors with cement significantly improves the health of young children measured by decreases in the incidence of parasitic infestations, diarrhea, and the prevalence of anemia, and an improvement in children's cognitive development. Additionally, we find significant improvements in adult welfare measured by increased satisfaction with their housing and quality of life, as well as by lower scores on depression and perceived stress scales.